Hurwitz rational functions - Barkovsky, Yury; Tyaglov, Mikhail (Linear algebra and its applications, 2011)
A generalization of Hurwitz stable polynomials to real rational functions is considered. We establish an analog of the Hurwitz stability criterion for rational functions and introduce a new type of determinants that can be treated as a generalization of the Hurwitz determinants.